Efforts to Develop the Management of Educator and Educational Personnel Standards in Maritime Vocational Education - Utami, Prapti; Pambudi, M Aji Luhur; Winarsih; Retno Haryanti; Ali Khamdilah (Nama Jurnal Akmi, 2025)
Abstract The national education system of Indonesia aims to enlighten the nation's life by developing students' potential into individuals who are faithful, morally upright, healthy, capable, creative, independent, and responsible democratic citizens. The educational framework includes curriculum, teaching methods, evaluation, and management of educational institutions designed to shape character and moral values. Although the government has established National Education Standards related to the qualifications and competencies of educators and educational personnel, various issues still exist in their development and management. Therefore, new innovations are necessary to achieve holistic quality education. Purpose – This research aims to determine the qualification standards and competencies of educators in maritime education as well as understand the evaluation and supervision standards applied. Methodology – The research method employs a qualitative approach with literature analysis from various regulations related to higher vocational maritime education in Indonesia. Findings – The findings indicate that changes in educator standards are crucial for maintaining relevance with rapid developments in the maritime industry regarding technology and regulations. This change process involves analyzing industry needs up to continuous evaluation. However, challenges such as limited qualifications of educators; inability of standards to respond to changes; ineffective evaluation systems; lack of oversight; limited access to professional training; and misalignment between programs need addressing. Originality – Continuous professional training for educators must be conducted so that graduates possess skills aligned with industry needs in maritime sectors